Consensus on the Rational Use of Antithrombotics in Veterinary Critical Care (CURATIVE): Domain 5—Discontinuation of anticoagulant therapy in small animals. Issue 1 (17th January 2019) - Brainard, Benjamin M.; Buriko, Yekaterina; Good, Jennifer; Ralph, Alan G.; Rozanski, Elizabeth A.
Abstract: Objectives: To systematically evaluate the evidence supporting the timing and mechanisms of permanent or temporary discontinuation of antiplatelet or anticoagulant medications in small animals Design: Standardized, systematic evaluation of the literature, categorization of relevant articles according to level of evidence and quality (poor, fair, or good), and development of consensus on conclusions via a Delphi‐style survey for application of the concepts to clinical practice. Settings: Academic and referral veterinary medical centers. Results: Databases searched included Medline via PubMed and CAB abstracts. Two specific courses of inquiry were pursued, one focused on appropriate approaches to use for small animal patients receiving antiplatelet or anticoagulant drugs and requiring temporary discontinuation of this therapy for the purposes of invasive procedures (eg, surgery), and the other aimed at decision‐making for the complete discontinuation of anticoagulant medications. In addition, the most appropriate methodology for discontinuation of heparins was addressed. Conclusions: To better define specific patient groups, a risk stratification characterization was developed. It is recommended to continue anticoagulant therapy through invasive procedures in patients at high risk for thrombosis that are receiving anticoagulant therapy, while consideration for discontinuation in patients with low to moderate risk of thrombosis is reasonable. In patients with thrombosis in whom the underlying cause for thrombosis has resolved, indefinite treatment with anticoagulant medication is not recommended. If the underlying cause is unknown or untreatable, anticoagulant medication should be continued indefinitely. Unfractionated heparin therapy should be slowly tapered rather than discontinued abruptly.